Rights in Criminal Law in the Light of a Will Theory. Issue 3 (2nd September 2019) - Moser, Elias
Abstract : The will theory of rights has so far been considered incapable of capturing individual rights under criminal law. Adherents of the will theory, therefore, have defended the claim that criminal law does not assign rights to individuals. In this article I argue first, that criminal law does assign individual rights and second, that the will theory of rights may enhance our understanding of these rights. The two major implications of the account are: a volenti non fit iniuria principle for criminal law, and a theoretical framework for an idea of punishment as restitution.